Generic masculine nouns and pronouns perceived as linguistic tools for excluding women - Čejková, Andrea (2007)
The thesis focuses on a controversial feature of the English language, on generic masculine nouns and pronouns. It centres on those theories which suggest that the use of generic masculine terms is not neutral, causes male-bias and thus is sexist. The aim of the thesis is to find out what arguments the opponents of the generic masculine have to deny its neutrality. The thesis describes various theories proposing that he/man language causes male-biased imagery and thus linguistically excludes women; and that it has irrefutable impact on the whole society as well as on individuals (mainly women). It also deals with various researches and studies which provide a mass of vital evidence of the opinion that generic masculine nouns and pronouns are discriminating means of sexist language. These researches also demonstrate what negative effects he/ man language has. The present research should verify the presupposition stating that generic masculine terms do not provoke generic thoughts.